Comparative analyses of the hemostatic efficacy and surgical device performance of powdered oxidized regenerated cellulose and starch-based powder formulations - Marianne Stark; Allen Y. Wang; Brittny Corrigan; Henok G. Woldu; Samar Azizighannad; Gustavo Cipolla; Richard Kocharian; Hector De Leon (Research and Practice in Thrombosis and Haemostasis)
Background: Hemostatic powders offer unique therapeutic advantages over other formulations, including ease of application and rapid distribution over large bleeding surfaces. The efficacy of powder-based hemostats is dependent on device performance, which is rarely investigated independently from efficacy. Objectives: The current study aimed to compare the hemostatic efficacy of an oxidized regenerated cellulose agent (Surgicel, Ethicon, Inc) and 3 starch-based biopolymers (Arista, Becton Dickinson; PerClot, Baxter International; and 4DryField, PlantTec Medical GmbH) and the performance of their delivery device applicators. Methods: Efficacy was evaluated in a porcine model of bleeding using 2 study designs where the powder was delivered with (experiment 1) and without (experiment 2) device applicators. Device performance (powder expression) was examined in vitro at 3 device positions/angles: 90° (vertical, downward), 45° (slanted, downward), and 180° (horizontal). Results: Surgicel efficacy rate was noninferior (P ≤ .0002) and superior (P ≤ .004) to that of any of the 3 starch-based agents regardless of whether the powder was delivered with their devices (experiment 1) or directly applied onto the bleeding sites (experiment 2). Surgicel required fewer applications (P ≤ .0002) and less powder (P < .0001) to achieve hemostasis. The Surgicel device was the only one that consistently delivered precise amounts of powder over a critical range of applications in the 3 positions tested. Conclusion: The oxidized regenerated cellulose powder was the most efficacious hemostat, and the Surgicel applicator exhibited the highest performance compared with any of the 3 starch-based devices investigated. The current study highlights the relevance of combining high-efficacy powder hemostats with innovative, high-performance applicators to effectively manage bleeding control in surgical settings.